Determinants of seeking advice within defined contribution retirement savings schemes. (28th August 2018) - Clark, Gordon L.; Fiaschetti, Maurizio; Gerrans, Paul
Abstract: We report results from a study of superannuation member advice‐seeking within their plan, explaining observed patterns by member age, gender, issue salience and size‐of‐bet effect. Inquiry mode, frequency and volume of contact with the advice‐provider, and sensitivity of members to legislative change and macroeconomic events are considered. Results show that gender (female more likely than male), age (older rather than younger), balance (larger rather than smaller) and experience (longer rather than shorter) are the strongest advice‐seeking predictors, consistent over time. Findings suggest member engagement around retirement planning may be more effective when considering the factors affecting advice‐seeking behaviour in general.